Asthmatic lung fibroblasts promote type 2 immune responses via endoplasmic reticulum stress response dependent thymic stromal lymphopoietin secretion - Drake, Li Y.; Koloko Ngassie, Maunick Lefin; Roos, Benjamin B.; Teske, Jacob J.; Prakash, Y. S. (Frontiers in Physiology, 2023)
Lung fibroblasts contribute to asthma pathology partly through modulation of the immune environment in the airway. Tumor necrosis factor-α (TNFα) expression is upregulated in asthmatic lungs. How asthmatic lung fibroblasts respond to TNFα stimulation and subsequently regulate immune responses is not well understood. Endoplasmic reticulum (ER) stress and unfolded protein responses (UPR) play important roles in asthma, but their functional roles are still under investigation. In this study, we investigated TNFα-induced cytokine production in primary lung fibroblasts from asthmatic vs. non-asthmatic human subjects, and downstream effects on type 2 immune responses. TNFα significantly upregulated IL-6, IL-8, C-C motif chemokine ligand 5 (CCL5), and thymic stromal lymphopoietin (TSLP) mRNA expression and protein secretion by lung fibroblasts. Asthmatic lung fibroblasts secreted higher levels of TSLP which promoted IL-33-induced IL-5 and IL-13 production by peripheral blood mononuclear cells. TNFα exposure enhanced expression of ER stress/UPR pathways in both asthmatic and non-asthmatic lung fibroblasts, especially inositol-requiring protein 1α in asthmatics. ER stress/UPR inhibitors decreased IL-6, CCL5, and TSLP protein secretion by asthmatic lung fibroblasts. Our data suggest that TNFα and lung fibroblasts form an important axis in asthmatic lungs to promote asthmatic inflammation that can be attenuated by inhibiting ER stress/UPR pathway.